Selected Topics in WiMAX - Pasolini, Gianni (IntechOpen, 2013)
In June 2001, operators and equipment vendors in the communications ecosystem founded the nonprofit WiMAX Forum, an industry-led organization aimed at harmonizing broadband wireless access standards. Nowadays, about 10 years later, the WiMAX technology is a mature and affordable solution for high-speed IP-based 4G mobile broadband, fully supporting bandwidth-intensive services,such as high-speed Internet access and television, as well as less bandwidth-demanding but more latency-sensitive services, such as voice-over-IP calls. In this book a collection of selected papers is presented, which covers several aspects of the WiMAX technology, with particular reference to multiuser multiple input multiple output diversity techniques,peak-to-average power ratio, mesh architectures, handover mechanisms, coordinated authentication in a heterogeneous network environment and multicast /broadcast re-keying algorithms.